Assessing export competitiveness of Indian groundnut - Murlidhar Meena; K A Khunt; H N Meena; H T Khorajiya (Agricultural Economics Research Review, 2023)
This paper examines export competitiveness of Indian groundnut during the period 1996-97 to 2013-14 using PAM. Results shows that export of groundnut from India is highly competitive and has great potential in international market. The measured values of NPC, EPC and ESC have been less than unity throughout the period. DRCR also remains below unity pointing towards efficient utilisation of domestic resources in groundnut cultivation. Positive social profit all through the years reveals social welfare gain. Groundnut export is found generating resources to the Indian economy as the measured total policy transfer is negative.